(untitled) (Research, Society and Development, 2020)
Mortality rates from prostate cancer in Brazil are increasing, one of the main challenges to early detection of prostate cancer is the lack of knowledge about its natural history, as well as the encouragement of known measures for early detection. This study aims to identify and analyze the knowledge of men treated at the health clinic of a college in Belém, about prostate cancer and prevention, is characterized as descriptive-analytical with a qualitative approach. The participants were 10 men treated at the outpatient clinic of a college in Belém, over a period of two months. Data collection took place after approval by the Ethics Committee. To obtain the data, a semi-structured interview was conducted, conducted by a script with 5 questions, 11 referring to the profile of the actors and 5 questions specific to the object investigated. The content analysis technique was used in the interviews, with three analytical categories emerging: Knowledge of men about Prostate Cancer; Need for guidance on the prevention of prostate cancer; Beliefs and Taboos regarding prostate cancer. It was evidenced that the majority of the interviewees are not aware of the prevention methods, in addition, the studied group did not know how to identify the risk factors associated with prostate cancer. There was also a difficulty in assimilating knowledge with preventive practices. It was clear the need for nurses to invest in the health education process about prostate cancer, providing information on risk factors and aspects related to changes that may occur in the prostate and how preventive exams are performed and the age recommended for the beginning of this period. control.